2007
DOI: 10.1074/jbc.m608750200
|View full text |Cite
|
Sign up to set email alerts
|

Picornavirus Internal Ribosome Entry Site Elements Can Stimulate Translation of Upstream Genes

Abstract: Certain viral and cellular mRNAs initiate translation capindependently at internal ribosome entry site (IRES) elements. Picornavirus IRES elements are widely used in dicistronic or multicistronic vectors in gene therapy, virus replicon systems, and analysis of IRES function. In such vectors, expression of the upstream gene often serves as internal control to standardize the readings of IRES-driven downstream reporter activity. Picornaviral IRES elements translate optimally at up to 120 mM K ؉ concentration, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
2
20
1
Order By: Relevance
“…Therefore, BLucB is eIF4F, and thus, BTE dependent. Finally, observations that some plant and mammalian virus IRESes can stimulate translation of upstream AUGs (Jaag et al 2003;Herbreteau et al 2005;Nicholson et al 2006;Junemann et al 2007) may be explained by mechanisms similar to that shown in Figure 7.…”
Section: A Model For Bte-mediated Cap-independent Translationmentioning
confidence: 81%
“…Therefore, BLucB is eIF4F, and thus, BTE dependent. Finally, observations that some plant and mammalian virus IRESes can stimulate translation of upstream AUGs (Jaag et al 2003;Herbreteau et al 2005;Nicholson et al 2006;Junemann et al 2007) may be explained by mechanisms similar to that shown in Figure 7.…”
Section: A Model For Bte-mediated Cap-independent Translationmentioning
confidence: 81%
“…Recently, Junemann et al (32) showed that translation can initiate at a cistron located upstream of picornavirus IRESs. These results would require the ribosomal subunits to initiate translation up to Ϸ900 nt upstream of the IRES.…”
Section: Discussionmentioning
confidence: 99%
“…Our concerns came from our finding that picornavirus IRES elements can stimulate the translation not only of the gene downstream of the IRES but also that of an upstream gene. 23 A picornavirus IRES in a dicistronic mRNA system can bind translation initiation factors and ribosomes and hand them over to the upstream translation start site. From the above study it was clear to us that we must take care when interpreting results obtained in the carbohydrate and lipid metabolism of the liver.…”
Section: Microrna-122 Stimulates Hcv Translationmentioning
confidence: 99%